Knowledge, attitude, and practices of the community about Chikungunya in selected Districts of Afar Region, Northeast Ethiopia; its implications for controlling the disease: a community-based quantitative and qualitative cross-sectional study - Biruk Zerfu; Tesfu Kassa; Gezahegne Mamo; Mengistu Legesse (BMC Public Health, 2024)
Abstract Background Chikungunya (CHIK) is a viral disease spread by Aedes mosquitoes in tropical and subtropical countries, including Ethiopia. It is important to educate communities and implement behavioral and social interventions to prevent and control the spread of disease. This study assessed the community’s knowledge, attitude, and practices (KAP) about CHIK disease in the Afar Region, Northeast Ethiopia. Methods A community-based quantitative and qualitative cross-sectional study was conducted between September 2022 and January 2023 in two districts in the Afar Region, Ethiopia. A household survey (HHS) using a structured questionnaire was conducted through face-to-face interviews for the quantitative study. For the qualitative research, focus group discussions (FGDs) were conducted using a semi-structured questionnaire. Data was analyzed using descriptive statistics, Pearson’s correlation coefficient, and multiple linear regressions. Results The study included 296 and 116 adult community members for quantitative and qualitative studies, respectively. Of 296 respondents, 67.3% had previously heard of CHIK, and of those who heard of it, 44.7% knew that CHIK is caused by a virus. While a majority (68.8%) of participants believed that CHIK could be prevented, only 45.6% considered it a serious illness. Additionally, over half (56.8%) of the respondents knew that not all mosquitoes transmit CHIK. About 48.7% were able to identify the Aedes mosquito, but only 16.5% of those knew that Aedes mosquitoes bite during the daytime. The overall mean correct/positive response scores for knowledge, attitudes, and practices were 63.2%, 60.0%, and 60.0%, respectively. Being a student and having educational levels of grade 9-12th and college or above were associated with good knowledge while being single, having an educational level of 9-12th, and being within the age group of 45–59 years old were found to be associated with positive attitude scores. Conclusion The study revealed a limited understanding of CHIK and the role of the Aedes mosquito in the study area. The community had uncertainty about the disease, its transmission, and prevention measures. The lack of understanding may affect attitudes towards the disease and risk perceptions, leading to less practice in prevention and control measures. The findings suggest the need for community-based educational initiatives to improve awareness and promote prevention and control measures.